Lock-in amplifier as an alternative for reading Radio-Frequency identification (RFID) tags in sensing applications - De Lima, Guilherme R. [UNESP]; Gozzi, Giovani [UNESP]; Fugikawa-Santos, Lucas [UNESP] (Taylor & Francis, 2021)
High-frequency (HF) radio-frequency identification (RFIDs) tags can be combined to electrodes coated with semiconducting thin-films to produce low-cost and disposable sensors with wireless capabilities. Mobile phone applications generally use near-field connection (NFC) to read chip digital information, providing discrete information from the device. To obtain a continuous analogic reading, more sophisticated equipment such as spectrum analyzers are needed. In the present article, we describe a method to obtain the frequency response spectrum of RFID tags using synchronous detection via a lock-in amplifier. The tags were coupled to interdigitated electrodes coated with semiconducting metal oxides (SMOs) to produce UV-sensors and with semiconducting polymer polyaniline (Pani) as chemically responsive wireless devices for the proof-of-concept of the developed method.
Keywords: chemical sensing; lock-in amplifier; Radio-frequency identification (RFID) tags; thin-films; ultraviolet (UV) sensing